النظـــام القانوني لأجهزة الإستثمار في التشريع الجزائري - راضية سحاب; بشرى جباري (My University, 2022)
Summary: Algerian legislators have established various investment development agencies, the most important of which are: the National Investment Council, the National Investment Agency and the National Agency for Real Estate Brokerage and Control. These agencies work on a common objective: to attract investors and attract capital in order to improve the investment climate in Algeria and to move economic development forward by following a legal system designed by Algerian legislators. ……………………… الملخص : انشأ المشرع الجزائري أجهزة مختلفة لتطوير الإستثمار أهمها : المجلس الوطني للإستثمار، والوكالة الوطنية للإستثمار بإضافة للوكالة الوطنية للوساطة و الضبط العقاري تعمل هذه الأجهزة على هدف مشترك ألا وهو جذب المستثمرين واستقطاب رؤوس الأموال عملا على تحسين مناخ الاستثمار في الجزائر وتحريك عجلة التنمية الإقتصادية بتباع نظام قانوني في التسيير موضوع من طرف المشرع الجزائري ……………………… Résumé : Les législateurs algériens ont mis en place diverses agences de développement de l’investissement, dont les plus importantes sont : le Conseil national d’investissement, l’Agence nationale d’investissement et l’Agence nationale pour le courtage et le contrôle immobiliers. Ces agences travaillent sur un objectif commun : attirer les investisseurs et attirer les capitaux afin d’améliorer le climat d’investissement en Algérie et de faire avancer le développement économique en suivant un système juridique conçu par les législateurs algériens.